Morphotropic Phase Boundary in Solution‐Derived (Bi0.5Na0.5)1−xBaxTiO3 Thin Films: Part I Crystalline Structure and Compositional Depth Profile. Issue 4 (23rd December 2013) - Pérez‐Mezcua, Dulce; Sirera, Rafael; Bretos, Iñigo; Ricote, Jesús; Jimenez, Ricardo; Fuentes‐Cobas, Luis; Escobar‐Galindo, Ramón; Chateigner, Daniel; Lourdes Calzada, M.; Damjanovic, D.
<x xml:space="preserve">Abstract</x> In this work, ferroelectric (Bi0.5Na0.5)1−xBaxTiO3 thin films were fabricated by chemical solution deposition (CSD) with compositions x = 0.050–0.150. Stoichiometric thin films (hereinafter BNBT) and others containing 10 mol% excesses of Bi3+ and Na+ (BNBTxs) were spin coated onto Pt/TiO2/SiO2/(100)Si substrates and crystallized by rapid thermal processing at 650°C for 60 s in oxygen atmosphere. Crystalline structure is studied by X‐ray diffraction using Cu anode (λCu = 1.5406 Ǻ) and synchrotron radiation (λ = 0.97354 Ǻ). Rietveld refinement showed the coexistence of rhombohedral/tetragonal phases in the BNBT films for x values close to those reported for (Bi0.5Na0.5)1−xBaxTiO3 bulk ceramics. Different volume fractions of the rhombohedral/tetragonal phases are detected as a function of the Ba2+ content. An apparent shift of the position of the morphotropic phase boundary (MPB) is observed in the BNBTxs films. Here, the MPB region appears for nominal Ba2+ molar values of x ~ 0.10 and the experiments using a grazing‐incidence synchrotron radiation indicate the existence of a crystalline phase with pyrochlore structure at the film surface. Rutherford backscattering experiments (RBS) revealed that the bismuth excess is not volatilized during the crystallization of the BNBTxs films which present inhomogeneous compositional depth profile and thick BixPt bottom interfaces. The MPB BNBT films with x ~ 0.055 have a homogeneous compositional depth profile without appreciable bottom interfaces. Scanning electron micrographs reveal less porosity and higher grain sizes in the stoichiometric films than in those with Bi3+ and Na+ excesses.